2015
DOI: 10.1177/0333102415584308
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of the CGRP receptor antagonist telcagepant for prevention of headache in women with perimenstrual migraine

Abstract: Telcagepant 140 mg taken perimenstrually for seven days was generally well tolerated, but was associated with transaminase elevations. Telcagepant did not reduce monthly headache frequency, but did reduce perimenstrual headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 19 publications
(39 reference statements)
1
67
0
1
Order By: Relevance
“…These animals also had renal damage that was independent from the increase in blood pressure [35]. Related with these findings, acute intravenous (i.v.)…”
Section: Tips 1346 No Of Pages 10mentioning
confidence: 57%
See 2 more Smart Citations
“…These animals also had renal damage that was independent from the increase in blood pressure [35]. Related with these findings, acute intravenous (i.v.)…”
Section: Tips 1346 No Of Pages 10mentioning
confidence: 57%
“…The cardiovascular effects of long-term blockade of the CGRP receptor with gepants were assessed in only two, relatively small and short-lasting, prophylactic treatment studies [34,35]. Little is known about the cardiovascular safety of the long-term blockade of the CGRP system with CGRP (receptor) antibodies.…”
Section: Cardiovascular Safety Of Blocking the Cgrp Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A telcagepant preventive twice daily dosing study reported patients with clinically significantly liver function test (LFT) increases . A second study using telcagepant in prevention of menstrual migraine also suggested a potential liver problem, and the drug development program was stopped …”
Section: Small Molecule Cgrp Receptor Antagonists (Gepants)mentioning
confidence: 99%
“…Though clinical trials of some CGRP antagonists (like Tolcegipant) have not demonstrated measurable clinical benefit as migraine treatments, CGRP receptor antagonists continue to show potential as anti-nociceptive agents that function without directly affecting inflammatory pathways [20]. …”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%